Project management - Salam, Sazilah; Mohd Sanusi, Nurazlina; Khalid, Fararishah; Yusof, Robiah; Wan Mohd Ghazali, Khadijah; Buyong, Edna (Desktop Publisher, 2009)
Project Management has been an established field for many years. Managing IT project management in general and other projects such as network, software and interactive media project management in specific requires ideas and information that go beyond a standard project management. Effective project management ensures that a project is completed on time, within budget and with high quality.